Influence of pelvic floor disorders on quality of life in women - Rocío Adriana Peinado Molina; Antonio Hernández Martínez; Sergio Martínez Vázquez; Juan Miguel Martínez Galiano; Juan Miguel Martínez Galiano (Frontiers Media S.A., 2023)
ObjectiveTo determine whether the different pelvic floor disorders are associated with changes in perceived quality of life (QoL), globally and in its sub-dimensions.MethodsAn observational study was conducted with women in Spain between 2021 and 2022. Information was collected using a self-developed questionnaire on sociodemographic data, employment, history and health status, lifestyle and habits, obstetric history, and health problems. The SF-12 questionnaire was used to assess quality of life. The Pelvic Floor Distress Inventory (PFDI-20) was used to assess the presence and impact of pelvic floor problems, and includes the POPDI-6 subscales for prolapse, CRADI- 8 for colorectal symptoms, and UDI-6 for urinary symptoms. Crude (MD) and adjusted mean differences (aMD) were estimated with their respective 95% confidence intervals (CI).ResultsThousand four hundred and forty six women participated in the study with a mean age of 44.27 (SD = 14.68). A statistical association was observed between all the pelvic floor disorders and QoL, overall and in all its dimensions (p <0.001), in the bivariable analysis. The lowest scores were observed in the emotional component. After adjusting for confounding factors, the pelvic floor disorders in general (aMD −0.21, 95% CI: −0.23 to −0.20), the impact of uterine prolapse symptoms (aMD −0.20, 95% CI: −0.27 to −0.12), the colorectal-anal symptoms (aMD −0.15, 95% CI: −0.22 to −0.09), and urinary symptoms (aMD −0.07, 95% CI: −0.13 to −0.03) was negatively associated on the score on the SF-12 questionnaire (p <0.05).ConclusionsWomen who have a pelvic floor dysfunction, symptoms of pelvic organ prolapse, colorectal-anal symptoms, or urinary symptoms, have a worse perceived quality of life in all dimensions. Prolapse symptoms have the biggest impact, and the emotional component of QoL is the most affected sub-domains.